Pengembangan Media Edukatif Make a Match terhadap Keterampilan Sosial Siswa Menengah Pertama: Development of Make a Match Educational Media for Junior High School Students' Social Skills - Venia Ramadhani; Hendro Yulius Suryo Putro; Ali Rachman (ITScience (Information Technology and Science), 2025)
Social skills are an important competency that needs to be developed in junior high school students. However, in learning practice, educational media that encourage active student interaction, communication, and cooperation remain needed. Given these conditions, it is necessary to develop learning media that capture students' attention and support the process. This research was conducted using a research and development approach through the 4D model stages, namely define, design, develop, and disseminate. The media developed was an educational game card titled